2019
DOI: 10.2319/101718-750.1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of Orthodontic Treatment Outcomes of Mild Skeletal Class III Malocclusion Between Facemask and Facemask in Combination with a Miniscrew For Anchorage in Growing Patients: A Single-center, Prospective Randomized Controlled trial

Abstract: Objectives: To investigate the hypothesis that there is difference in the treatment outcomes of milder skeletal Class III malocclusion between facemask and facemask in combination with a miniscrew in growing patients. Materials and Methods: Patients were randomly divided into two groups. In one group, the patients were treated with facemask therapy (FM group: 12 males, eight females, average age: 10 years, 5 months ± 1 year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
30
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 18 publications
13
30
2
2
Order By: Relevance
“…Two hundred and eighty-three studies that did not correspond with the inclusion criteria were excluded based on the title and abstract. After reading the full text of the 35 studies, 18 studies (four RCTs 11 , 14 - 16 and 14 CCTs 4 , 7 , 8 , 10 , 12 , 17 - 25 ) involving a total of 667 patients were finally included. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow diagram is given in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hundred and eighty-three studies that did not correspond with the inclusion criteria were excluded based on the title and abstract. After reading the full text of the 35 studies, 18 studies (four RCTs 11 , 14 - 16 and 14 CCTs 4 , 7 , 8 , 10 , 12 , 17 - 25 ) involving a total of 667 patients were finally included. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow diagram is given in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Different types of modified skeletal anchorage devices have been applied for maxillary protraction in the orthodontic clinic, 10 , 11 including the Hybrid Hyrax RME appliance. 12 However, these studies have not clarified whether appliances that combine tooth and bone anchorage provide better treatment effects than those using bone anchorage alone.…”
Section: Introductionmentioning
confidence: 99%
“…Maxillary protraction with a facemask often causes tilted compensations of the upper and lower incisors. 18,19 Chen et al found that maxillary protraction, when performed during the late-mixed There were no significant differences between the different dentition stage groups in terms of SNB, indicating that mandibular growth was difficult to control. 3 Studies have shown that the orthopaedic force transformed the growth direction of the mandible, 21 promoted the clockwise rotation of the mandible and increased the height of the lower face.…”
Section: Discussionmentioning
confidence: 99%
“…FM therapy with a palatal miniscrew for anchorage may promote more maxillary forward growth than FM therapy alone. 23 However, skeletal anchorageassisted FM therapy may not be recommended for patients in primary and early mixed dentitions.…”
Section: Discussionmentioning
confidence: 99%